Kangaroo Method for Low Birth Weight Infants: Case Study - Purwanto, Nofita Setiorini Futri; Sapia, Noni (CV. Literasi Publikasi Indonesia, 2024)
Low Birth Weight (LBW) is a birth weight of less than 2500 grams, which increases the risk of neonatal morbidity and mortality. Babies with low birth weight are more susceptible to complications. Babies with low birth weight increase the risk of health complications such as infection, hypothermia and growth disorders. The kangaroo method for babies with low birth weight is an appropriate alternative method that is simple and cheap. This case study aims to analyze midwifery care for low birth weight patients. The author uses a descriptive analytical method in the form of a case study approach to midwifery care for patients which includes assessment, midwifery diagnosis, midwifery planning, midwifery implementation, midwifery evaluation and use of Evidence Based Practice (EBP) interventions. The results of the evaluation can be resolved, this is indicated by the patient's weight gain and stable body temperature. This shows that the kangaroo method is an effective method and has been proven to increase body weight in patients who experienced low birth weigh.